Perancangan Tata Letak Toko Ritel Berdasarkan Pola Belanja Konsumen Dengan Market Basket Analysis (Studi Kasus: Indomaret Sukatani) - Hartanto, Nadiya Hasna Fakhirah; Aribowo, Budi (Universitas Al Azhar Indonesia, 2023)
During the pandemic in early 2020, consumer behavior in shopping at retail stores changed. Some of the main factors taken into consideration that can influence consumer shopping behavior are facilities, layout, and time spent shopping. This can affect product sales at Indomaret Sukatani which has an ineffective layout so that it is difficult for customers to reach and customers need to spend a long-time shopping. To solve these problems, it is necessary to do data mining using the Market Basket Analysis method with the Apriorist and FP-Growth Algorithm so that customer shopping patterns can be known in order to design new layouts. Then the effectiveness test can be done by calculating the rectilinear distance to find out the most optimal layout design, namely the layout design based on the FP-Growth Algorithm with the smallest total rectilinear distance value of 2353.5 in the first scenario, 2313 in the second scenario, and 1609.5 in the third scenario.Keywords – Customer Behaviour, Layout, Market Basket Analysis